Renewable energy systems : the Earthscan expert guide to renewable energy technologies for home and business - Jenkins, Dilwyn (Earthscan expert series., 2013)
This book is the long awaited guide for anyone interested in renewables at home or work. It sweeps away scores of common misconceptions while clearly illustrating the best in renewable and energy efficiency technologies. A fully illustrated guide to renewable energy for the home and small business, the book provides an expert overview of precisely which sustainable energy technologies are appropriate for wide-spread domestic and small business application. The sections on different renewable energy options provide detailed descriptions of each technology along with case studies, installation diagrams and colour photographs, showing precisely what is possible for the average household. The chapter on how to select the renewable technology most appropriate for ordinary homes and businesses summarizes this analysis in a neat and easy to use table and demonstrates with examples exactly how to assess your local renewable resources.